1979
DOI: 10.3109/07435807909070883
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal Rhythm of Pituitary-Thyroid Axis in Male Rats and the Effect of Adrenalectomy

Abstract: Levels of TSH, thyroxine (T4) and triiodothyronine (T3) were measured by radioimmunoassay in plasma (TSH, T4, T3) and pituitary (TSH) of 60-day old male Long-Evans rats. Definite diurnal rhythms were demonstrated in pituitary TSH, plasma TSH and T3 in intact rats, evidenced by the statistically significant differences between zenith and nadir for pituitary TSH, plasma TSH and T3. The zenith value of pituitary TSH and the nadir values of plasma TSH, T4 and T3 were observed at the same time (2400 h) as were the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

1981
1981
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 28 publications
0
3
0
1
Order By: Relevance
“…rats) in which hypothyroidism decreases and hyperthyroidism in creases spontaneous motor activity [10] as well as gross brain excitability [26,34,35]. In some species, thyroid hor mones are also involved in the maintenance of various states of cyclic behavior, from running activity to hiberna tion [16,23,29], and themselves undergo characteristic cyc lic changes such as circadian rhythmicity [27], That thyroid activity is implicated in the maintenance of specific charac teristics of sleep organization is not surprising although sys tematic studies in support of this relationship are rare. In humans, sleep stages 3 and 4 and paradoxical sleep are markedly shortened or absent in hypothyroidism [20,25,39] but prolonged in hyperthyroidism (especially sleep stages 3 and 4).…”
mentioning
confidence: 99%
“…rats) in which hypothyroidism decreases and hyperthyroidism in creases spontaneous motor activity [10] as well as gross brain excitability [26,34,35]. In some species, thyroid hor mones are also involved in the maintenance of various states of cyclic behavior, from running activity to hiberna tion [16,23,29], and themselves undergo characteristic cyc lic changes such as circadian rhythmicity [27], That thyroid activity is implicated in the maintenance of specific charac teristics of sleep organization is not surprising although sys tematic studies in support of this relationship are rare. In humans, sleep stages 3 and 4 and paradoxical sleep are markedly shortened or absent in hypothyroidism [20,25,39] but prolonged in hyperthyroidism (especially sleep stages 3 and 4).…”
mentioning
confidence: 99%
“…Although only two time points were studied, and a complete profile of the 24 h secretion pattern of TSH was not measured, the present study suggests that the circadian variation of serum TSH is main¬ tained in adult animals made hypothyroid neo¬ natally. Although we have not previously studied whe¬ ther there is a circadian variation of T4 in adult animals, Ooka-Souda et al (1979) reported that there is a circadian fluctuation of serum T4 levels in adult rats, with morning values being lower than afternoon T4 levels. We also found an elevation of the serum T4 concentration at 13.00 h compared to 07.00 h serum values in the control animals, but not in the neonatally treated animals.…”
Section: Discussionmentioning
confidence: 91%
“…Adrenalectomy not only reduced plasma corticosterone levels to almost zero, but also decreased plasma T3 and T4 levels, but diurnal rhythms of the HPT axis did not depend on rhythms of the HPA axis [73]. In pregnant female rats adrenalectomized on gestation day 8 there was a decrease in TRH mRNA, increase in serum TSH, and a decrease of T3 only in females [74]; it appears that maternal glucocorticoids determine the development of the hypothalamic-pituitary-thyroid axis in progeny.…”
Section: Thyroid Gland Function Under Impaired Adrenal Functionsmentioning
confidence: 93%